Diagnostic strategy for trigger identification in severe reactive hemophagocytic lymphohistiocytosis: A diagnostic accuracy study. Issue 1 (1st November 2020) - Tudesq, Jean‐Jacques; Valade, Sandrine; Galicier, Lionel; Zafrani, Lara; Boutboul, David; de Bazelaire, Cédric; Munoz‐Bongrand, Nicolas; Canet, Emmanuel; Ardisson, Fanny; Lemiale, Virginie; Darmon, Michael; Azoulay, Elie; et al.
Abstract: Reactive hemophagocytic lymphohistiocytosis (rHLH) management requires early recognition, trigger identification, and adequate treatment in order to reduce mortality. We assessed the diagnostic yield of tissue biopsies to identify trigger in severe rHLH. We included all consecutive patients presenting an rHLH diagnosis (HLH‐2004 criteria) admitted to the intensive care unit (ICU) of a tertiary hospital. This retrospective diagnostic accuracy study was conducted according to the Standards for Reporting Diagnostic Accuracy Statement. Among the 134 included patients (median age 47 years [IQR 47–56]), an underlying immunodeficiency was previously known in 61.2%. rHLH trigger was identified in 127 patients (94.8%) (hematological disorder 75%, infection 16%, systemic disease 4%). Diagnostic yield of tissue biopsies was as follows: lymph node 75% (95% confidence interval [CI], 61–85), skin 50% (95% CI, 27–73), bone marrow 44% (95% CI, 34–55), liver 30% (95% CI, 15–49). Splenectomy (yield 77%; 95% CI, 46–95) was reserved to cases of diagnostic deadlock. Procedural severe adverse events included two cases of reversible hemorrhagic shock. Seventy‐eight percent of patients received etoposide regarding to the rHLH severity, and 68% could receive trigger‐specific treatment in the ICU. A comprehensive diagnostic workup led to an rHLH trigger identification in 95% of patients, allowing prompt initiation of appropriate therapy. Prospective studies to validate a standardized diagnostic approach are warranted.